Patient Characteristics Associated with NPO (Nil Per Os) Non-Compliance in the Pediatric Surgical Population - Ghimire A; Maves GS; Kim SS; Raman VT; Tobias JD (Dove Medical Press, 2022)
Anuranjan Ghimire,1 Gregory S Maves,1,2 Stephani S Kim,1,2 Vidya T Raman,1,2 Joseph D Tobias1,2 1Department of Anesthesiology & Pain Medicine, Nationwide Children's Hospital, Columbus, OH, USA; 2Department of Anesthesiology & Pain Medicine, the Ohio State University College of Medicine, Columbus, OH, USACorrespondence: Anuranjan Ghimire, Department of Anesthesiology & Pain Medicine, Nationwide Children's Hospital, 700 Children's Dr, Columbus, OH, 43235, USA, Tel +1 614-722-4200, Fax: +1 614-722-4203, Email Anuranjan.Ghimire@nationwidechildrens.orgIntroduction: Cancellation of surgery or delay on the day of service is a huge burden for the patient, family, and healthcare system. Preventable delays impact efficiency and workflow, which may increase costs due to overtime and idle rooms during peak hours. Non-compliance to nil per os (NPO) guidelines remains one of the most common preventable causes for surgical cancellations. The current study sought to investigate and understand patient factors that may be associated with non-compliance to NPO guidelines.Methods: After IRB approval, a retrospective review of completed and cancelled pediatric procedures requiring the use of anesthesia over a 5-year period was performed. Emergency procedures and inpatient surgeries were excluded. Data regarding patient demographics and surgical service were extracted from the electronic medical records for comparison. A logistic regression model was used to identify factors associated with cancellations due to NPO non-compliance.Results: There were 825 cancellations due to NPO non-compliance of 144,049 cases for an incidence of 0.57% over the 5-year period. Patients in the 6- 12 year old age range and those who self-identified as non-White or non-English speaking had a higher incidence of cancelling due to NPO non-compliance. Compared to ear, nose, and throat (ENT) procedures, cancellations due to NPO non-compliance were more likely in radiology, dental, and urology procedures.Discussion: Many factors may impact a family's compliance with NPO guidelines. Patient-related factors included those who self-identified as non-White or non-English speaking. Patients having ENT surgery were less likely to have NPO non-compliance than those having radiologic procedures, dental surgery, or urologic surgery. Future interventions focused on these groups may be most effective in limiting day of surgery cancellations.Keywords: nil per os, pediatric anesthesia, cancellation